Structure and Properties of Coatings Formed by Detonation Spraying of Titanium Powder; IOP Conference Series: Materials Science and Engineering; Vol. 286 : Modern Technologies and Materials of New Generations (MTMNG-2017) - Panin S. V. Sergey Viktorovich; Vlasov I. V. Ilya Viktorovich; Stankevich R. V.; Dudina D. V.; Ulyanitsky V. Yu.; Batraev I. S. (2018, 2018)
Title screen